APLICATION OF MEDICINAL BIOMAGNETISM IN THE TREATMENT OF OBESITY AND WEIGHT LOSS: A CASE STUDY - Oliveira dos Santos, Cristina; Terezinha Idalêncio Detroz, Nelci; Mara Rambo Martini, Angela; Cecchele Lima Vanzella, Bruna; Viapiana Bossa, Adriane; Cabral de Azevedo, Caroline (Health and Society, 2024)
Obesity is now considered a public health problem. It is treated as a chronic disease where the accumulation of body fat occurs due to several factors, such as complex morphological changes resulting from the interaction of lifestyle, genetic and emotional factors. Therefore, the need for therapies that help to improve the quality of life of people with this disease becomes quite viable. This study was carried out with the objective of describing the Medicinal Biomagnetism (MB) therapy helping obese individuals to lose weight. There are numerous scientific research aimed at studying the causes of the development of obesity. There is a variety of “recipes”, medicines, therapies, formulas, proteins, diets, etc., in order to treat obesity. These techniques are usually offered at a high cost, and are almost always not performed correctly, so they do not have the desired effects. In this research, we present a possibility of low- cost, non-invasive therapy, called Medicinal Biomagnetism that uses medium intensity magnets with the objective of providing not only quality of life, but also assisting in weight loss. In this research, the 3D movement protocol 1, 3D movement protocol 2 and specific special pairs were used. The result achieved so far gives us hope that it is possible to lose weight without the use of any medication and with a low investment cost, considering the health gain obtained by the patient.